solutions for b

# Xm xm proof in the above e x do substitution t

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: identity in (2) with respect to t, over 1 Ex = √ t=0 1 √ t 1−t 0, 1 : dt π − ∞ 2 m − 3 !! 1 m=1 2 m !! t=0 √ tm √ t 1−t 2m − 1 2m !! dt π !! 2 = (4) π − 2 m − 3 !! ∞ π 2m − 1 2 m=1 2 m !! Prove that the integral in (3): 1 = Ex t=0 √ 1 − tx √√ t 1−t dt has the following alternative expression: π 2 u=0 2 1− sin u 14 2 x du. xm . xm Proof. √ In the above E x , do substitution √ t = sin u, 1−t = cos u, and t= sin u dt = 2 sin u 2 . cos u Then d u. Hence Ex 1− π 2 = π 2 = 2 u=0 (5) 1− x 2 sin u u=0 2 sin u sin u cos u cos u 2 sin u x du. We may evaluate the iniﬁnite series 2 2 m − 3 !! ∞ 2m − 1 2 m=1 2 m !! as follows. By (3), 2 = Ex Substitute π−π x=1 ∞ 2 m − 3 !! 2m − 1 2 m=1 2 m !! xm . into this result: 2 ( ∗) E1 = π−π 2 m − 3 !! ∞ 2 m=1 2 m !! 15 2m − 1 . du We may easily calculate the left-hand side of (∗) as follows: √ 1 − t ·1 √√ t 1−t 1 E1 = t=0 1 = √ t=0 1 t=0 = 2 √ √ 1−t √ t 1−t 1 √ t = dt dt dt 1 t t=0 =2 In short, E1 = 2. √ 1 −2 √ 0 = 2. Substitute this back into (∗): 2 2 = π−π 2 m − 3 !! ∞ 2 m=1 2 m !! From this we conclude that the value of the inﬁnite series 2 ∞ 2 m − 3 !! 2 m=1 2 m !! equals 1− 16 2 . π 2m − 1 2m − 1 ....
View Full Document

## This note was uploaded on 01/12/2014 for the course MATH 116 taught by Professor Scholle,minho during the Fall '08 term at Kansas.

Ask a homework question - tutors are online